Adolescent sexual and reproductive health needs and utilisation of health services in the Bono East Region, Ghana - Joshua Okyere; Naomi Kyeremaa Yeboa; Charity Nikoi; Margaret Owusu-Amoako; Listowel Ferka; Anastasia Nurzhynska; Joshua Amo-Adjei (BMC, 2024)
Abstract Background Adolescents in Ghana are vulnerable to unequal power relations at the personal, community and structural levels which in turn limits their opportunities in access to critical sexual and reproductive health information and services. There is therefore high unmet need for sexual and reproductive health (SRH) information and services and the Bono East region typifies this situation, recording some of the poorest SRHR outcomes among adolescents. We, therefore, aimed to investigate the SRH needs (unmet), behaviors and utilization of SRH services among adolescents in the Bono East region. Methods Using a maximum variation sampling approach, this qualitative study conducted in-depth interviews and focused group discussions with adolescent boys and girls, parents, community leaders, and healthcare providers. Results Our findings are presented under two broad categories: major SRHR concerns of adolescents, and perspectives about that influences adolescents' utilization of SRHR services. Under the major SRHR need of adolescents, the following themes emerged: information and services on pregnancy prevention, menstrual hygiene management, availability of comprehensive abortion care services, and attitudes towards adolescent pregnancy. The perspectives about the factors that influence adolescent children were discussed at multiple levels: individual/personal. interpersonal and community/societal. At the individual level, limited understanding of adolescence/puberty, desire of adolescents to belong and misperceptions about contraceptives. At the interpersonal level, issues relating to technical capacity needs of service providers, disrespect exhibited by service providers, and parental failure were identified as influential factors. Then at the community/societal level, we identified structural constraints and compromised social safety concerns in accessing contraceptives and services. Conclusion In conclusion, the findings from this study offer valuable insights into the complex landscape of adolescent sexual and reproductive health in the Bono East region. The implications for policy and practice are manifold, ranging from comprehensive education to addressing menstrual hygiene, involving parents, training healthcare providers, and promoting respectful care.